Determinants of foreign portfolio investments: BRICS as a unit of analysis - Tsaurai, Kunofiwa (Acta Universitatis Danubius. Œconomica, 2022)
The determinants of foreign portfolio investment in BRICS (Brazil, Russia, India, China, South Africa) was examined in this study using panel data (1998-2020) analysis methods such as Fully Modified Ordinary Least Squares (FMOLS), fixed effects and pooled ordinary least squares (OLS). What necessitated the author to undertake this study is that the existing literature on the determinants of foreign portfolio investment is full of gaps. This study is all focused on trying to fill these gaps, already enunciated in the introductory section. Economic growth under the fixed effects had a significant positive influence on foreign portfolio investment. Also, the FMOLS show that savings’ impact on foreign portfolio investment was observed to be significantly positive. The pooled OLS also indicates that stock market development had a positive and significant effect on foreign portfolio investment. Finally, human capital development’s influence on foreign portfolio investment was observed to significantly negative under the FMOLS approach. The study therefore encourages BRICS authorities to implement policies aimed at increasing economic growth, stock market development and savings to attract more foreign portfolio investment.